Analisis Validitas Sistem Penyajian Modul Fisika berbasis PBL Pada Materi Gerak Melingkar Beraturan dan Penerapannnya - Halimatus Sa'diyah; Jalis Syarifah; Ria Arista; Yusinta Dewi Amalia Putri; Galuh Rahma Eka Wati; Ajeng Putri Utami; Novi Fitri Rahmadani; Naila Dewi U; I Ketut Mahardika; Subiki Subiki (Jurnal Ilmiah Wahana Pendidikan, 2023)
Modules play an important role in learning, especially in physics subjects. Validity testing is conducted to assess the suitability of a teaching module. A module is considered valid when validators have declared it to be so. In this case, the researcher aims to analyze the validity of the presentation system of a problem-based learning (PBL) physics module on Circular Motion and its Applications. The method used is descriptive-qualitative. The descriptive-qualitative method is employed to describe the validity and suitability of the presentation system of the PBL-based physics module on Circular Motion and its Applications. This way, it can be determined whether the created physics module's presentation system is valid. Based on the validation results of the 'Physics Teaching Module Based on Problem-Based Learning (PBL) on Circular Motion and its Applications,' it is stated that this module meets the criteria for presentation and has been revised based on suggestions and feedback from the validator